Synthesis, Characterization and Evaluation of Some Pyranopyrazole Derivatives as Multifunction Additives for Medium Lubricating Oils - Salih, Ahmad R.; Al-Messri, Zainab A. K. (Iraqi Journal of Science, 2022)
The current work involves synthesis of 6-amino-4-(4-hydroxyl-3-methoxyphenyl)-3-methyl-1-phenyl-1,4- dihydropyrano[2,3-c]pyrazole-5-carbonitrile (2) by condensation of 2-(4-hydroxyl-3-methoxybenzylidine) malononitrile (1) with 3-methyl-1-phenyl-2-pyrazolin-5-one. The product 2 was then reacted with various aldehydes to form a series of Schiff base derivatives 3a-h. The reaction of the chosen Schiff base derivatives (3a and 3b) with mercaptoacetic acid gave thiazolidinone derivatives (4a and 4b). The structures of prepared compounds were confirmed using FT-IR, 1H NMR, and 13C NMR spectroscopies.  They were evaluated as good copper corrosion inhibitors, anti-rust, and antioxidants. This was done by mixing them with the base medium lubricating oil (type 60 stock) provided by the Iraqi Midland Refineries Company/Al-Daura according to the American Society of Testing and Materials ASTM-D130, ASTM-D665, and Institute of Petroleum's testing method, oxidation stability test (IP-280), respectively.